Mewujudkan Pelayanan Publik Inklusif: Implementasi Jalur Terpisah bagi Pemohon Disabilitas dan Literasi Teknologi Terbatas - Manurung, Mario Pandapotan; Anida Sri Rahayu Mastur, Salsabila Andi Jani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Digital transformation through the M-Passport application has made passport applications easier, but still presents challenges for applicants with disabilities and those with limited technological literacy. This situation prompted innovation in the form of a separate pathway at the Pematangsiantar Class II Immigration Office as an effort to create more inclusive public services. The research employed a mixed-methods approach, using questionnaires, interviews, and observations. The separate pathway was implemented through direct assistance from officers who effectively assist vulnerable groups. Supporting factors include good internal communication, employee competence, and a positive disposition in the form of empathy. Barriers include limited outreach, inadequate human resources, and infrastructure. In conclusion, the separate pathway needs to be strengthened through regulations and resource support to become the standard for inclusive public services throughout Indonesia.